Dynamique de la neige de culture dans les Alpes Françaises - Pierre Spandre; Hugues François; Samuel Morin; Emmanuelle George-Marcelpoil (Revue de Géographie Alpine)
Snowmaking facilities have been commonplace in the French Alps since 1974 and particularly since the 1990s. Now, nearly all resorts are equipped with snowmaking facilities, which guarantee snow for skiers and sufficient revenue for resorts. The effects of climate change have justified recent investments in new facilities, and research efforts are beginning to combine socio-economic and physically-based approaches. We carried out a survey in autumn 2014, collecting data from a representative sample of resorts in the French Alps. We found that 32% of maintained ski slope areas in the French Alps are now equipped with snowmaking facilities; our findings indicate that this proportion is likely to reach 43% by 2020, with most of the increase in “Very Large” resorts. Although “Medium” to “Very Large” resorts are currently equipped at similar levels, the projected development varies with resort size. “Very Large” resorts are planning the largest growth, with nearly 50% of their ski slopes equipped with snowmaking facilities by 2020. However, our analysis reveals a limited potential for snowmaking in the French Alps: since the 1960s, suitable conditions have decreased by several hours per year. Since the effects of climate change are expected to increase in the coming decades (all scenarios suggest an air temperature increase), ski resorts will have to produce snow in less ideal conditions, incurring greater costs as a result of decreased production efficiency.